Development and validation of a LC- MS/MS Method for simultaneous quantitation of telmisartan and pioglitazone in rat plasma - Das, Arindam; Sengupta, Pinaki; Ibrahim, Fuzianna; Chatterjee, Bappaditya; Mandal, Uttam Kumar (2016)
In majority of complex diseases like diabetes, multiple medications are essential to achieve the better therapeutic control, as several mediators are involved in their pathogenesis. Likewise, although the primary component of diabetes care is to control blood glucose level, management of cardiovascular risk factors should also be considered as vital one. Literature review reveals that the major and common health problems associated with pathophysiological mechanism for arterial damage in diabetes is hypertension. It is well established that angiotensin receptor blocker (ARB) class of antihypertensives are better tolerated antihypertensive. Amongst ARBs, telmisartan has fewer drug-related adverse events and provides superior blood pressure control. On the other hand, pioglitazone is a useful therapeutic drug for type 2 diabetes having beneficial pleiotropic effects on cardiovascular diseases. Thus, the combination therapy of telmisartan and pioglitazone can be beneficial to treat a patient suffering from diabetes and hypertension. A simple, high throughput and specific high-performance liquid chromatography tandem mass spectrometry (LC-MS/MS) method has been developed and validated according to the United States Food and Drug Administration (USFDA) guidelines for simultaneous quantification of telmisartan and pioglitazone in rat plasma. The bioanalytical method consists in the liquid-liquid extraction and quantitation by triple quadrupole mass spectrometer (API- 2000) using electrospray ionization technique, operating in multiple reaction monitoring (MRM) mode. The compounds were eluted isocratically injecting the aliquots of the processed samples on a C18 column with a mobile phase consisting of a mixture aqueous and organic phase. The ion transitions were monitored for the m/z ratio of telmisartan and pioglitazone. The response to telmisartan and pioglitazone was a linear function (r =0.99) of concentration over the entire linearity range. The validation results demonstrated that the method had satisfactory precision and accuracy across the calibration range. The Relative standard deviation (RSD) for intra- andinter-day precision was below 10%. The accuracy determined at three quality control levels was within 85 to 115%. This developed method proved reproducible and sensitive and can be used successfully to support a pharmacokinetic study. There was no evidence of instability of the analytes in rat plasma following stability studies.